The Role of Creativity in Moderating the Effect of Entrepreneurial Experience on Product Innovation: A Study on Startups in Indonesia - Putri, Shalsa Dita Yana; Maulani, Galih Abdul Fatah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2025)
The study discussed how the experience of entrepreneurs affected product innovation in Indonesian startup entrepreneurs through creative variables. The entrepreneurial experience plays a crucial role in an undertaking's starting capability or an occupational goal of this study is to test and anal yze the impact an entrepreneurial experience might have on product innovation capabilities in Indonesian startup entrepreneurs moderating creativity variables. Sampling techniques are using random sampling techniques with the responders of 30 people, Indonesia's starting up business. The analysis tool used what is smart PLS v. 3.2.7 by shem's method of analysis. Results in this study suggest that the experience of entrepreneurship does not significantly affect product innovation, the experience of entrepreneurship influences significantly to creativity, creativity influences significantly to product innovation, and the experience of entrepreneurship impacts to the ability of product innovation through creativity variables. Then it may be concluded that entrepreneurial experience affects the ability of product innovation through creative variables.